Pertumbuhan dan hasil genotipe kedelai (Glycine max (L.) Merril) pada tiga tingkat cekaman kekeringan - Nia Romania Patriyawaty; Gatut W. Anggara (Fakultas Pertanian Universitas Yudharta Pasuruan, 2020)
Drought stress is a major constraint to the production and yield stability of soybean (Glycine max (L.) Merr). Drought stress at the generative phase had a negative impact on soybean potential yield significantly. This study evaluated variation in five soybean genotypes (G1, G2, G3, G4 and G5) in their response to the three levels (100% of field capacity (D1), 80% from field capacity (D2) and 60% from field capacity (D3)) of drought stress in a glass house. This study was arranged in a factorial randomized completely block design with three replications. Results showed that all five genotypes responded significantly (P<0.05) to the drought stress treatments in soybean yield. The average yield was respectively reduced by 8.4% and 11.6% in the D2 and D3 treatments, respectively, compared to the D1 (control). Percent reduction of yield for genotype G4 (19.8%) was lower compared to other genotypes. This is indicated that genotype G4 tolerance to drought stress. The evaluation on the morphological character was potentially to become a screening tool for soybean breeding program.